Evapotranspiration-Based Irrigation Scheduling for Agriculture - Isaya Kisekka; Kati W. Migliaccio; Michael D. Dukes; Bruce Schaffer; Jonathan H. Crane; Haimanote K. Bayabil; Sandra M. Guzman (EDIS)
AE457, a 6-page fact sheet by Isaya Kisekka, Kati W. Migliaccio, Michael D. Dukes, Jonathan H. Crane, and Bruce Schaffer, focuses on the main concepts related to ET-based irrigation scheduling and reviews the use of "smart" irrigation scheduling controllers for agricultural applications. Includes references.